2021
DOI: 10.1177/17479541211031170
|View full text |Cite
|
Sign up to set email alerts
|

Can discreet performance banding, as compared to bio-banding, discriminate technical skills in male adolescent soccer players? A preliminary investigation

Abstract: Maturation-related changes in body dimensions and performance can lead to physical mismatches and drop out from youth sport. Here, we propose a new method termed ‘discreet performance banding’ (DPB). We aimed to determine if dividing youths by actual physical performance of a discreet skill or ability (‘change or direction’ [COD] ability) could discriminate between the most and least skilled players better than a marker of implied performance, such as an assessment of biological maturation. 182 male academy Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…That said, it has also been demonstrated that maturity miss-matched (pre-PHV vs post-PHV, pre-PHV vs circa-PHV, post-PHV vs circa-PHV) bio-banded formats may afford players (particularly later maturing players) the opportunity to demonstrate important psychological characteristics [ 1 , 2 ], which are perhaps more readily identifiable during difficult playing environments when players are faced with adversity or problematic scenarios which are experienced during mixed-maturity match formats [ 26 ]. However, despite clear evidence to suggest that bio-banding is being embraced within academy soccer programmes [ 26 , 28 31 , 35 ], it is currently unclear to what extent bio-banding is being used, how it is being used, and for what purpose. In addition, for bio-banding to be applied more broadly across academy soccer programmes, it is also important for policy makers and prospective research designers to understand the situational and environmental factors which practitioners are confronted with when attempting to apply bio-banding match formats.…”
Section: Introductionmentioning
confidence: 99%
“…That said, it has also been demonstrated that maturity miss-matched (pre-PHV vs post-PHV, pre-PHV vs circa-PHV, post-PHV vs circa-PHV) bio-banded formats may afford players (particularly later maturing players) the opportunity to demonstrate important psychological characteristics [ 1 , 2 ], which are perhaps more readily identifiable during difficult playing environments when players are faced with adversity or problematic scenarios which are experienced during mixed-maturity match formats [ 26 ]. However, despite clear evidence to suggest that bio-banding is being embraced within academy soccer programmes [ 26 , 28 31 , 35 ], it is currently unclear to what extent bio-banding is being used, how it is being used, and for what purpose. In addition, for bio-banding to be applied more broadly across academy soccer programmes, it is also important for policy makers and prospective research designers to understand the situational and environmental factors which practitioners are confronted with when attempting to apply bio-banding match formats.…”
Section: Introductionmentioning
confidence: 99%
“…It also appears that, at the population level, their relatively younger peers are more likely to continue through the TD system to elite performance. Yet, to this point, much of the extant literature has focused on 'solving' a variety of early advantage effects by focusing on levelling the playing field, for example: biobanding [25]; age order shirt banding [26]; birthday banding [27], performance banding [28] and corrective adjustment procedures [29]. Yet, very little attention has been paid to the dropout rates of those with earlier advantage [30] and investigation of underpinning mechanisms is disappointingly sparse.…”
Section: Mechanismsmentioning
confidence: 99%
“…In essence, we are suggesting that if we are to offer truly practical implications to support the growth of a research-informed profession [80], the field should begin considering relative advantage or disadvantage on a holistic biopsychosocial basis, rather than using discreet indicators (e.g., maturation and/or relative age) alone. Notably, recent evidence has taken steps towards alternative approaches to levelling of the playing field with players being banded by technical competence [28]. In addition, there have been suggestions that coaches use a variety of methods for the grouping of players to provide a broad range of experiences for the player [28].…”
Section: Applied Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grouping of athletes according to their maturation status, rather than chronological age is commonly referred to as bio-banding [4,5,7]. The exclusive [8] objective of bio-banding is to reduce between player maturity-related differences in anthropometric [9], and physical fitness characteristics, and create a more equitable playing and training environment [10][11][12][13][14][15][16][17]. Bio-banding has been shown to be an effective strategy to reduce the large within group variations associated with the early development of maturity-related anthropometric characteristics, such as stature and body-mass [1,2] which can be directly associated to the maturation process [9].…”
Section: Introductionmentioning
confidence: 99%